Relación entre el nivel de conocimientos tributarios y la comisión de delitos tributarios en los comerciantes del mercado Modelo 3 de octubre 2019 - Vento Urresty, Vicky Ivette (2021)
In the present research work entitled "Relationship between the level of tax knowledge and the commission of tax crimes in the merchants of the Model Market October 3, 2019", the objective was to determine the relationship that exists between the level of tax knowledge of the merchants of the October 3 Model Market and the commission of tax crimes, having formulated the main hypothesis that the level of tax knowledge in the October 3 Model Market merchants is direct with the commission of tax crimes; According to the analysis of the information collected through the questionnaire applied to the merchants of the Model Market October 3, 2019, it is concluded that: the main hypothesis is rejected, since it was determined that there is an indirect relationship between tax knowledge and commission of tax crimes. The specific hypothesis is accepted since it was determined that the level of tax knowledge and tax crimes in the merchants of the Model Market October 3, 2019, is High.